The relationship between the level of physical activity, body mass index, and vertical jump in students aged 15 to 17 years (Research, Society and Development, 2024)
This research aimed to compare the vertical jump height using the Sargent Jump Test, the Body Mass Index (BMI), and the weekly physical activity level of students aged 15 to 17 from a public school in northeastern Rio Grande do Sul. The method used to achieve the proposed objective was a cross-sectional qualitative and quantitative approach, calculated using Pearson's correlation and the Student's t-test. The study revealed a progressive increase in BMI with age, a tendency for students with higher BMI to perform worse in the vertical jump test, and a prevalence of males in height, higher BMI percentages, and jump power. The theoretical contribution stemmed from the expansion of the concepts addressed from a complementary perspective. The practical contribution manifested through the discovery of empirical data with the potential to assist teaching practices. It concludes that it is essential to encourage healthy physical activity habits among young people to prevent health problems related to overweight and sedentary lifestyles.